"They Don't Really Care About Us!" On Political Worldviews in Popular Music. Issue 1 (23rd August 2012) - Franke, Ulrich; Schiltz, Kaspar
Abstract : Both political activism by pop musicians and the discussion of popular culture in international relations (IR) have been on the rise in recent years. A closer look at the political meaning of mainstream pop songs, however, is still missing. Therefore, we examine the political worldviews that become manifest in the lyrics of US and German top ten hits from 1960 to 2009. A remarkable feature of these worldviews is the rejection of political institutions and actors in a mood of alienation and disenchantment, along with a strong appeal to the responsibility of individuals to autonomously tackle societal deficiencies. This appeal is based on a pronounced trust in people's capacity to solve problems jointly and without any interference by institutionalized politics. In this context, the growing recognition of political activism by so‐called celebrity diplomats may be linked to these worldviews. Reflections on normative implications of the political worldviews, in turn, raise delicate questions about legitimate agency and the way public affairs are organized.